STRATEGI MANAJEMEN SUMBER DAYA INSANI PADA PROSES KONVERSI BPR MUSTAQIM ACEH (Analisis Realitas dan Idealitas Kualifikasi Sumber Daya Insani Berdasarkan Nilai-Nilai Islam) - Nafisah, Raudhatun (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2020)
BPR Mustaqim Bank needs to prepare its human resources (HR) to be success in the conversion process from conventional to sharia system. However, the major problem is that it lacks of qualified HR who is competent (have capabilities in the field of economy and sharia), and has Islamic characters. The objective of this study was then to elaborate the concept of human resources management with Islamic values to achieve qualification and strategy of human resource management during the conversion process of BPR Mustaqim Bank. This study carried out qualitative approach by using descriptive method. It involved classifying and describing qualifications of the HR, both qualifications determined by the bank and ideal qualifications in line with Islamic values required by the bank for the successful conversion process to sharia system. Based on the reality, the HR qualification in BPR Mustaqim Bank are not fully ideal yet, either in terms of the HR qualification or the HR management strategy. In the aspect of HR qualification, BPR Mustaqim Bank should optimize the knowledge of the HR on sharia banking, and improve their religiosity by conducting religious activities. Meanwhile, to improve HR management strategy, BPR Mustaqim Bank should perform recruitment, selection, training and development process, compensation, and employee performance appraisal and relationship in line with the conversion purposes, in which the application procedure is adjusted to Islamic values.